Degradation Study Of Sofosbuvir In Bulk Drug And Tablet Dosage Form By RP-High Performance Liquid Chromatography - D.Pati, Sushil; A. Beldar, Kareemoddin (International Journal of Psychosocial Rehabilitation, 2020)
Sofosbuvir were subjected to forced degradation conditions and the formed degradation products were well separated and resolved from the drug and excipients on SunFire C18 column (250 × 4.6 mm, 5 μ) using blend of Acetonitrile: Water (70: 30 v/v) pH 7.0 in isocratic mode at a flow rate of 0.8mL/min at an ambient temperature of 28 °C with the detection wavelength at 260nm. The retention time of Sofosbuvir was found 3.22 min. The linearity was performed in the concentration range of 20-100 ppm with correlation factor of 0.999 for Sofosbuvir. The percentage purity of Sofosbuvir tablet was found 99.98%. The drug was found to degrade under acid, alkali and oxidative condition but found stable under dry heat and photolytic conditions.